Acute Oral Toxicity of Methanolic Extracts from the Fruit and Leaf of Parijoto (Medinilla speciosa Blume) in Mice - Annisa Farida Muti; Refian Ariesta Eka Maulana; Dhigna Luthfiyani Citra Pradana; Eldiza Puji Rahmi (Journal of Pharmascience, 2026)
Medinilla speciosa Blume, or parijoto, contains flavonoids, saponins, alkaloids, and tannins with pharmacological potential. However, information regarding its safety profile, particularly acute toxicity data, is still very limited, so research is needed to evaluate its safety level. This study aims to evaluate the acute oral toxicity of M. speciosa leaf and fruit extracts in ddY mice. This study used a true experimental design. M. speciosa leaf and fruit extracts were obtained by ultrasonic-assisted extraction with methanol as a solvent. The acute oral toxicity test was conducted with a fixed-dose method at a single dose of 2000 mg/kgBW. Parameters observed for 14 days included mortality, clinical symptoms of toxicity, body weight changes, relative organ weights, and histopathological analysis of the liver and kidneys. The findings indicated an absence of fatalities across all treatment groups. The LD50 values for both extracts were determined to exceed 2000 mg/kgBW, categorising the fruit and leaf extracts as mildly toxic (category 5). Mild toxic symptoms were only observed in the treatment group receiving the fruit extract. Histopathological analysis of the liver and kidneys revealed mild cellular changes that were not statistically significant. Therefore, a single oral administration of M. speciosa fruit and leaf extracts at doses up to 2000 mg/kgBW is relatively safe.